Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 12. entitled if they were in want, and which at present average some 9/6 a week. It also seems relevant to note that the total cost of these services - which in 1913 amounted only to £66 millions and is today £432 millions — would, in 1965 under the "Beveridge" plan, become £858 millions and, in these circumstances, it is difficult to imagine that, in a country which has throughout been in the forefront in the providing of social services, increased expenditure of these dimensions is necessary for the Abolition of Want. (37) It is not suggested that the foregoing estimate of £40 millions is necessarily an exact measure of the cost which would have been necessary to abolish Want in this country in 1929, nor is it suggested that the whole of the £30 millions paid in Supplementary Old Age Pensions today can be treated as a corresponding deduction in that cost. (38) These figures are merely put forward as giving some idea of the dimensions of the problem of Want and, on the foregoing considerations, we are forced to the conclusion that by far the larger part of the additional expenditure involved in the "Beveridge" plan is attributable, not to the abolishing of Want, but to the making of payments to sections of the community who are not in Want. (39) Turning now to the question of how far that additional expenditure under the "Beveridge" plan would involve increased payments by the Employers and Taxpayer in addition to the increased payments by the Beneficiaries themselves, the position is shown in the following Table - Table "D" :- TABLE "D". 1938 1945 1965 Under "Beveridge" Under Existing Law Under "Beveridge" £ Mill. £ Mill. £ Mill. £ Mill. (a) Paid by Beneficiaries. 55 69 194 192 (b) " " Employers 66) 278 83) 348 137) 488 132) 651 ¡(c)" " Taxpayer..... 313) 265) 351) 519) (d) Balancing Items (Interest, etc.) 9 15 15 15 342 432 697 858 (40) It will be seen from the above Table that the sums to be paid by Employers and the Taxpayer to finance the "Beveridge" proposals would, in 1965, amount to £651/ 200/B/3/2/C216/5/50